Stoner - Williams, John, 1922-1994 (New York Review Books classics., 2003)
"William Stoner is born at the end of the nineteenth century into a dirt-poor Missouri farming family. Sent to the state university to study agronomy, he instead falls in love with English literature and embraces a scholar's life, so different from the hardscrabble existence he has known. And yet as the years pass, Stoner encounters a succession of disappointments: marriage into a 'proper' family estranges him from his parents; his career is stymied; his wife and daughter turn coldly away from him; a transforming experience of new love ends under threat of scandal. Driven ever deeper within himself, Stoner rediscovers the stoic silence of his forebears and confronts an essential solitude. John Williams's luminous and deeply moving novel is a work of quiet perfection. William Stoner emerges from it not only as an archetypal American, but as an unlikely existential hero, standing, like a figure in a painting by Edward Hopper, in stark relief against an unforgiving world."--from the back cover.